Sagot :
Réponse :
Explications étape par étape
Bonjour
Complète par l’entier relatif manquant :
• 10^(...) x 10^(-6) = 10^(-8)
10^(...-6) = 10^(-8)
... - 6 = -8
... = -8 + 6
... = -2
10^(-2) x 10^(-6) = 10^(-8)
• (10^(-6))^(...) = 10^12
10^(-6*...) = 10^12
-6 * ... = 12
... = 12/(-6)
... = -2
(10^(-6))^(-2) = 10^12
• 10^4/10^... = 10^(-3)
10^(4-...) = 10^(-3)
4 - ... = -3
4 + 3 = ...
... = 7
10^4/10^7 = 10^(-3)
• 2^4 x 5^4 = ...^4
(2 x 5)^4 = ...^4
10^4 = ...^4
... = 10
2^4 x 5^4 = 10^4
• 8^3/8^... = 8^(-2)
8^(3-...) = 8^(-2)
3 - ... = -2
... = 3 + 2
... = 5
8^3/8^5 = 8^(-2)
• (6^...)^(-9) = 6^(-45)
6^(...*(-9)) = 6^(-45)
... * (-9) = (-45)
... = -45/(-9)
... = 5
(6^5)^(-9) = 6^(-45)